Application of nickel cobalt oxide nanoflakes for electrochemical sensing of estriol in milk. Issue 70 (11th July 2016) - Fu, Hui-Jun; Wang, Yu; Dong, Xiu-Xiu; Liu, Yi-Xin; Chen, Zi-Jian; Shen, Yu-Dong; Yang, Chi; Dong, Jie-Xian; Xu, Zhen-Lin
Abstract : In this work, a nickel cobalt oxide (Ni/Co oxide) nanoflake based electrochemical sensor for the fast determination of estriol in milk is presented for the first time. Abstract : In this work, a nickel cobalt oxide (Ni/Co oxide) nanoflake based electrochemical sensor for the fast determination of estriol in milk is presented for the first time. Nanostructured Ni/Co oxide with controlled morphology was synthesized by a facile hydrothermal method. The morphology and the electrochemical performance of the Ni/Co oxide were characterized by scanning electron microscopy transmission electron microscope, and energy dispersive X-ray spectroscopy, respectively. Results indicated that the porous hexagonal sheet-like Ni/Co oxide exhibited excellent electrocatalytic activity toward estriol, with a low detection limit of 0.42 nM, and linear range from 1 nM to 14 nM. Good specificity, stability and reproducibility were also demonstrated. Recovery was determined from 92.7% to 103.7% for spiked milk samples, providing a promising platform for fast screening of estriol.